Supplementation with sodium selenite and selenium-enriched microalgae biomass show varying effects on blood enzymes activities, antioxidant response, and accumulation in common barbel (Barbus barbus) - Kouba, Antonín; Velíšek, Josef; Stará, Alžběta; Masojídek, Jiří; Kozák, Pavel (BioMed research international, 2014)
Yearling common barbel (Barbus barbus L.) were fed four purified casein-based diets for 6 weeks in outdoor cages. Besides control diet, these were supplemented with 0.3 mg kg(-1) dw selenium (Se) from sodium selenite, or 0.3 and 1.0 mg kg(-1) from Se-enriched microalgae biomass (Chlorella), a previously untested Se source for fish. Fish mortality, growth, Se accumulation in muscle and liver, and activity of selected enzymes in blood plasma, muscle, liver, and intestine were evaluated. There was no mortality, and no differences in fish growth, among groups. Se concentrations in muscle and liver, activity of alanine aminotransferase and creatine kinase in blood plasma, glutathione reductase (GR) in muscle, and GR and catalase in muscle and liver suggested that selenium from Se-enriched Chlorella is more readily accumulated and biologically active while being less toxic than sodium selenite.
Keywords: Liver; Animals; Antioxidants; selen; glutathionperoxidasa; játra; seleničitan sodný; Biomass; Animal Feed; Dietary Supplements; Cyprinidae; Sodium Selenite; mikrořasy; potravní doplňky; Glutathione Peroxidase; Selenium; antioxidancia; krmivo pro zvířata; zvířata; biomasa; Microalgae